Short Communication: Diversity and prevalence of ectoparasites associated with cultured fish from coal ponds in East Kalimantan, Indonesia - GINA SAPTIANI; CATUR AGUS PEBRIANTO; AGUSTINA AGUSTINA; ESTI HANDAYANI HARDI; FIKRI ARDHANI (Biodiversitas Journal of Biological Diversity, 2017)
Saptiani G, Pebrianto CA, Agustina, Hardi EH, Ardhani F. 2017. Short Communication: Diversity and prevalence of ectoparasites associated with cultured fish from coal ponds in East Kalimantan, Indonesia. Biodiversitas 18: 666-670. In East Kalimantan, coal pits are used for fish culture. The most fish species cultured in the coal ponds were carp and tilapia. The study aimed to identify ectoparasites types, diversity, and prevalence of fish cultured in coal ponds. Sampling was carried out between January and March 2016 on coal ponds in Kutai Kartanegara District, East Kalimantan. Samples were taken from two different coal ponds, but both coal ponds cultivated the same species of fish samples (carp and tilapia). The number of fish samples taken from coal ponds was 40 samples for each fish types in each location of coal ponds with the body weight of the fish samples between, 20-30 g. The preparation of parasite identification was conducted by taking every fish's external organ which was then scraped for microscopical preparation and observation. The identification of parasites was determined based on the morphological characteristics including the shape performances, specific spots and also the type of environment and habitat. The results showed that ectoparasites found in carp and tilapia cultured in coal ponds were Ichtyopthirius multifilis, Trichodina, Oodonium, Dactylogyrus, and Gyrodactylus, while Epistylis was only found in carp. The average percentage of ectoparasites prevalence in carp was from 30.00 to 59.17% with the attacked intensity was between 2.47 to 4.43 parasites/fish, while in tilapia was from 27.5 to 40.83% with the attacked intensity between 1.04 to 2.83 parasites/fish. The highest prevalence and intensity of parasite attacks was Trichodina in carp from a pond which has been used for a long time for fish culture. The prevalence and attacked intensity of ectoparasites on fish were higher in the longer use of coal ponds rather than those in new ponds.